2021
DOI: 10.3390/jcm10245925
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Coronary Artery Dissections: A Systematic Review

Abstract: Myocardial infarction with nonobstructive coronary artery disease due to spontaneous coronary artery dissection (SCAD) accounts for 5–8% of acute coronary syndrome (ACS) presentations. The demographic characteristics, risk factors, and management of patients with SCAD differ from those with atherosclerotic disease. The objective of this review is to provide a contemporary understanding of the epidemiology, pathophysiology, clinical presentation, and management of SCAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 57 publications
1
10
0
1
Order By: Relevance
“…Additionally, some patients had arrhythmias, cardiogenic shock, cardiac tamponade, and cardiac arrest. These presentations were also reported in previous studies [127].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Additionally, some patients had arrhythmias, cardiogenic shock, cardiac tamponade, and cardiac arrest. These presentations were also reported in previous studies [127].…”
Section: Discussionsupporting
confidence: 88%
“…Therefore, this raises the question of whether this is either a bias of smaller case reports/series or whether patients with a predisposing psychosocial trigger have a slightly more severe phenotype at presentation. Studies have revealed that performing PCI in SCAD patients is challenging, and its success rate is lower than that of PCI in atherosclerotic disease [9,127].…”
Section: Discussionmentioning
confidence: 99%
“…Intravascular ultrasound was not performed, but angiographic findings in combination with patient characteristics are thought to fit best with type 3 spontaneous coronary artery dissection (SCAD). 1 Computed tomography angiography of the head, chest, abdomen, and pelvis were without evidence of aneurysms elsewhere.
Figure 1 Electrocardiogram on Admission Electrocardiogram was remarkable for ST-segment elevations in II, III, aVF, and V 3 to V 6 —consistent with inferior and anterior ischemia.
…”
Section: Investigationsmentioning
confidence: 94%
“…Se debe considerar la limitación que se atribuye a la radiación en pacientes jóvenes y en el embarazo. La resolución espacial de la TC es subóptima para los vasos pequeños, lo que genera falsos negativos, y además las placas ateroscleróticas blandas pueden confundirse con un hematoma intramural 179 .…”
Section: Pregunta 5 ¿Qué Rol Tiene La Tc En El Seguimiento De Los Pac...unclassified